Analysis of Students’ Speaking Skill at Ninth Grade in Junior High School 2 Jambi City - Tiara Putri Hartanti; Nurul Fitri; Efa Silfia (JELT: Journal of English Language Teaching, 2022)
This study was conducted with the aim of analyzing students' speaking skills, at ninth grade in Junior High School 2 Jambi City. This research was designed using descriptive quantitative research methods. The population of this study was the ninth-grade students at Junior High School 2 Jambi City, and the sample was grade IX D students. This research uses a test as a research instrument. Then the test results are assessed and. The test used is an oral test with paired dialogue. The dialogue is made with the theme of "family" which is determined by This Research. The learning method through dialogue between friends was chosen because This Research saw students in one class often communicating verbally with their classmates to avoid embarrassment and fear so that students dared to express their opinions to their classmates. Thus, this courage will encourage students to do something, including the willingness to speak in English. The highest average test score is in the vocabulary component, which is 2,5 which means it is still "Poor." While the lowest test average value is found in the pronunciation component, namely 1,43 which means "very poor." The average test scores in the other four components are also in the "Poor" category, with the average grammar scores is 2,43, fluency 1,75, comprehension 2,12 and task 1,93. The average value explains that the speaking skill of students in grade ninth, especially in class IX D at Junior High School 2 Jambi City, is still classified as "Poor."